Pogranicze w ogniu (1992–1993) von Andrzej Konic, eine historische Fernsehserie als Kulturtext oder als Versuch, den „heiligen Krieg“ in der polnisch-deutschen Geschichte der Jahre 1917–1939 zu rekonstruieren - Mańke, Zbigniew (Poznańskie Studia Polonistyczne. Seria Literacka, 2023)
This article attempts to present the television series as a distinctive text which can persuasively and therefore effectively appeal to contemporary viewers, providing them with an insight into the events of a predefined period of Polish and German history, arousing certain emotions and thoughts or, in a general sense, even making them reflect on the history of both nations. With its attractive storyline based on, among other things, the dramaturgy of the presented events, this type of series can be perceived, to some extent, to be part of contemporary historical narration.